2016
DOI: 10.1093/mnras/stw240
|View full text |Cite
|
Sign up to set email alerts
|

External photoevaporation of protoplanetary discs in sparse stellar groups: the impact of dust growth

Abstract: We estimate the mass loss rates of photoevaporative winds launched from the outer edge of protoplanetary discs impinged by an ambient radiation field. We focus on mild/moderate environments (the number of stars in the group/cluster is N 50), and explore disc sizes ranging between 20 and 250 AU. We evaluate the steady-state structures of the photoevaporative winds by coupling temperature estimates obtained with a PDR code with 1D radial hydrodynamical equations. We also consider the impact of dust dragging and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
202
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(216 citation statements)
references
References 99 publications
9
202
1
Order By: Relevance
“…They suggested that this halo might be a remnant structure rather than being material driven out of the disc by photoevaporation. The photoevaporation interpretation was disfavoured based on the inferred low UV field and outer disk temperatures, which were well below those which had been previously considered by external photoevaporation models (Adams et al 2004;Facchini et al 2016). However, since this regime is previously unexplored it is difficult to conclude this with any certainty.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…They suggested that this halo might be a remnant structure rather than being material driven out of the disc by photoevaporation. The photoevaporation interpretation was disfavoured based on the inferred low UV field and outer disk temperatures, which were well below those which had been previously considered by external photoevaporation models (Adams et al 2004;Facchini et al 2016). However, since this regime is previously unexplored it is difficult to conclude this with any certainty.…”
Section: Introductionmentioning
confidence: 85%
“…For some time there has also been the theoretical expectation that protoplanetary discs might be significantly affected by more canonical radiation field strengths found in a cluster environment (e.g. Scally & Clarke 2001;Adams et al 2004;Holden et al 2011;Facchini et al 2016;Haworth et al 2016). This is now being directly supported by recent observations, such E-mail: t.haworth@imperial.ac.uk † Hubble fellow as those by Kim et al (2016) who identify proplyds irradiatied by a 3000 G 0 1 radiation field -approximately 100 times weaker than the field strengths irradiating classical proplyds (Störzer & Hollenbach 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant heating contribution in a PDR can readily be photoelectric heating from atomic layers of polycyclic aromatic hydrocarbons (PAHs, see e.g. Figure 2 of Facchini et al 2016), the abundance of which is highly uncertain, particularly towards the outer regions of discs (e.g. Geers et al 2006;Oliveira et al 2010;Perez-Becker & Chiang 2011).…”
Section: Photochemical-dynamics With Torus-3dpdrmentioning
confidence: 99%
“…the O stars). Furthermore there is the theoretical expectation of effective photoevaporation in lower radiation regimes (Adams et al 2004;Holden et al 2011;Facchini et al 2016). In particular, where the gravitational potential from the star is shallow, even very low UV fields can drive significant mass loss, as is expected for the large disc in IM Lup which is being irradiated by a field of only ∼ 4 G 0 (Cleeves et al 2016;Haworth et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The main physical mechanism driving disk dispersal in these harsh environments is thought to be photoevaporation driven by UV photons from the massive stars in the clusters (Johnstone et al 1998;Störzer & Hollenbach 1999;Richling & Yorke 2000;Clarke 2007;Anderson et al 2013;Facchini et al 2016). UV photons from massive stars ionize and heat the gas in the disk surface and induce a gas flow away from the disk when the sound speed of the gas exceeds the escape velocity (Johnstone et al 1998;Hollenbach et al 2000, p. 401).…”
Section: Introductionmentioning
confidence: 99%